Improving English Vocabulary in Fifth Grade Through Cooperative Learning with switch Games: A Case Study at MI GUPPI SUMBERWULAN - Rahmadani, Wanda Astria; Purwanto, Buntara Adi (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2025)
Vocabulary mastery is crucial for effective communication and understanding in English. In Indonesia, the Merdeka Curriculum promotes student-centered learning and emphasizes creativity and collaboration. However, many students find English challenging and struggle with vocabulary retention. To address this, a motivating approach is needed, such as Cooperative Learning using the Switch Game method. This method fosters group collaboration among students of varying abilities, enhancing interaction and making vocabulary learning enjoyable. The study aims to investigate the Implementation of this approach in improving elementary students' vocabulary mastery and recommendations for educators in designing effective learning strategies. The aim of this research is to explore the implementation of a cooperative learning method using the Switch Game to enrich vocabulary in English learning at the elementary school level. The study will involve various group activities with students of different abilities, promoting collaboration and knowledge sharing. Utilizing a quantitative pre-experimental design with pretest and posttest, the sample consists of 12 Student of fifth-grade students at MI GUPPI Sumberwulan,Selomerto. Data will be collected through vocabulary tests conducted before and after the cooperative learning implementation. The teacher's role will be to motivate and provide learning media. Students will participate in the Switch Game within a cooperative environment, making learning enjoyable. The expected outcome is an enrichment of vocabulary and increased motivation and interest in learning through interactive games, encouraging the development of student-centered and collaborative learning methods that enhance student outcomes.